Optimisation of Oil Palm Trunk Sap Fermentation to Bioethanol - Rossyuhaida, Mohd Zakria; Chua, Gek Kee; Jolius, Gimbun; Nor Shahirah, Mohd Nasir; Sook, Fun Pang; Mohd Fazli, Farida Asras; Ahmad Ziad, Sulaiman; Cheng, C. K.; Wan Asma, Ibrahim (2014)
Malaysia has an abundant amount oil palm biomass (approx. 15 million tons annually) arising from replanting activities involving old oil palm aged above 20 years-old which has lower productivity. In some cases, the outer hard portion of the oil palm trunk is utilised for plywood manufacturing, but the soft inner portion is normally discarded. This soft inner portion contains a huge amount of sugar-rich sap that can be fermented into bioethano,